2019
DOI: 10.1371/journal.pone.0213683
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance in difficult radial artery puncture for blood gas analysis: A prospective, randomized controlled trial

Abstract: BackgroundUltrasound (US) guidance has yet to prove its applicability in radial arterial blood gas analysis (ABGA) punctures. The main objective of our study was to compare the number of first-attempt successes (NFAS) for radial arterial puncture in difficult patients with or without US guidance. The Secondary aims were to compare the number of punctures (NOP), puncture time, and patient pain.MethodsIn this single-center, randomized controlled trial, patients who required a radial ABGA and in whom the arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…However, unlike the central vein, the diameter of the radial artery is small, and despite the use of ultrasound, its first-time success rate has not yet reached a satisfactory level. Therefore, in recent years, researchers have been trying to improve the ultrasound-guided radial artery puncture technique in order to improve the first-time success rate [ 32 ]. In clinical practice, with the rapid development and popularization of ultrasound technology, more and more operators will choose ultrasound salvage when they encounter difficulties in radial artery puncture, and even choose ultrasound guidance for the first operation.…”
Section: Related Workmentioning
confidence: 99%
“…However, unlike the central vein, the diameter of the radial artery is small, and despite the use of ultrasound, its first-time success rate has not yet reached a satisfactory level. Therefore, in recent years, researchers have been trying to improve the ultrasound-guided radial artery puncture technique in order to improve the first-time success rate [ 32 ]. In clinical practice, with the rapid development and popularization of ultrasound technology, more and more operators will choose ultrasound salvage when they encounter difficulties in radial artery puncture, and even choose ultrasound guidance for the first operation.…”
Section: Related Workmentioning
confidence: 99%
“…In our study, the median duration of puncture with CUD was 10 seconds, with a failure rate of 2%, while it was approximately 10% in a clinical study 2 and 47% in a clinical study on difficult patients 14 . The use of a simulation model facilitated the puncture because of the simplified anatomy and optimal condition of use without patient pain, anxiety, or unwanted movements.…”
Section: Discussionmentioning
confidence: 65%
“…US guidance has also improved radial artery catheterization success for angiographic procedures in cardiology 11,12 . For diagnostic radial artery puncture for blood gas analysis, US guidance did not ensure a significant benefit in the general population in studies conducted in emergency care units 2,13 but provided an improvement in difficult patients (ie, those with a nonpalpable radial artery or two previous puncture failures by a nurse) 14 . It also decreased the puncture duration and pain.…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported first-attempt success rates with the DNTP technique in adult patients were 83%[ 10 ] and 95% [ 15 ]. Grandpierre et al [ 28 ] showed that use of ultrasound improved the first-attempt success rate for radial artery puncture in patients with difficult-to-obtain radial arterial blood gas analysis, as defined by non-palpable radial arteries or two previous puncture failures. The use of ultrasound makes it more feasible to identify the radial artery in cases requiring multiple attempts.…”
Section: Discussionmentioning
confidence: 99%